On the method of detection the number and size of circuli on scales of pink salmon Oncorhynchus gorbuscha - Alexander M. Kaev; Alesya A. Pulkina (Известия ТИНРО, 2016)
Numbers of scale circuli are calculated and intercirculi spacings are measured along 3 radii (the longest one and two lateral ones deviated by 15o from the longest) for pink salmon Oncorhynchus gorbuscha from the Kurilsky Bay (Iturup Island, southern Kuril Islands) and the Ostrovka and Kura Rivers (southern Sakhalin Island). The difference of the circuli numbers along different radii was twice lower in comparison with the difference of their number between fish, but the differences of circulus spacing were similar between the radii and between fish in each area. Variability of these parameters was significantly higher between the areas, the differences were statistically significant for both in this case. The feature of low variability of the circuli number and intrecirculi spacing allows to pick a proper radius for measuring the circuli to avoid over- or underestimation of their number in cases of local deformation of scale (merging or splitting of some circuli).